Responding to crisis: The Cuban leadership copes with mass protests, 2020–2022 - Jorge I. Domínguez (International Journal of Cuban Studies)
How did the Cuban government and Communist Party respond to mass protests in 2020–2022? This article explores the official tools used to respond to such protests. Contrary to common perceptions, the government and the party did not merely repress their opponents. Instead, they combined repression with some economic, social, and political changes. Mass protests in Cuba 2020–2022 challenged the political order the most in 40 years. Repression, ‘socialist legality’, emigration, elements of political accountability, and selective political liberalisation targeting appeals to churches, LGBTQI+, and Afro-descendant groups were within the toolkit. There was also some liberalisation within the National Assembly and the Supreme Court as well as selective democratisation, submitting the draft Family Code to public discussion and referendum, permitting opposition. The enactment of limited market reforms, which had been first authorised ten years earlier, also accelerated.